The Influence of Small-Sided Games Training on Football Passing Accuracy in Dekate FC Bangkalan Players - Jamaluddin Imamy; Khoirul Anwar; Fajar Hidayatullah; Agus Himawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The passing technique is the technique most often used in football games. Passing is a technique for passing the ball between one player and another. The problem in this study is that many passes are not on target by players so the game becomes ineffective. Therefore, the purpose of this study was to determine the effect of small-sided games on improving the accuracy of football passing. This research is experimental research with a matching-only design. The research sample used was 20 players from the DESEAD FC Bangkalan team aged 12-14 years. The division of the experimental and control groups will use the MSOP technique. The results of the descriptive analysis of the experimental group obtained the mean pretest and mean posttest, while for the control group the mean pretest and mean posttest. For the results of the paired sample t-test in the experimental group, the Sig. 0.000 <0.05, so there is a significant difference between the pretest and posttest data. Meanwhile, in the control group Sig. 0.148 > 0.05 there was no significant difference in the pretest and posttest results of the control group. From the results of the independent sample t-test, the value of Sig. (2-tailed) 0.001 <0.05 There is a significant difference between the post-test results of the experimental group and the control group. For the percentage increase in data on passing test results, the experimental group had a significant increase of 21.59%. Meanwhile, the control group did not have a significant increase of 1.53%. So it can be concluded that small-sided games training is very influential in increasing the accuracy of football passing.